SOCIO-ECONOMIC CONTEXT OF SAVING BIODIVERSITY - GUL, Ejaz; CHAUDHRY, Imran Sharif (Journal of Environmental Management and Tourism; Vol 4 No 1 (2013): JEMT Volume IV Issue 1(7) Summer 2013, 2016)
Biodiversity provides a variety of socio- cultural and economic services for the humankind such as food, water, shelter, medicines, energy and aesthetic value. Pakistan is fortunate to have rich biodiversity canvas and is blessed with more than nine distinct ecological zones. These ecological zones provide a range of habitats to a great variety of flora and fauna, besides a vast variety of plant species having great medicinal and food value. However, deforestation, over development and lack of awareness has negative effects on biodiversity. These actions are leading to loss of species, habitats and degradation of ecosystems. Presently, rate of regeneration of resources is much slower than rate at which these natural assets are being consumed inducing a socio economic recession. There is a need to adopt a sustainable approach towards biodiversity conservation by establishing balance between gains and loss to bridge this gap between resource generation and consumption. Preservation of biodiversity without sustainability could impact the overall economic conditions leading to further poverty and affect the quality of life of people. This paper thoroughly reviews significance of biodiversity, its socio economic benefits and problems currently being faced to save this natural wealth.
Keywords: biodiversity, socio economic, sustainability, gains, loss, balance